A preliminary analysis of krakatau seismic data during the 1992/1993 eruptions - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT During the period of Anak Krakatau activity (started on November 1992), measurements of seismicity using a single vertical 1 Hz seismometer has been carried out. The data are transmitted to the 60 km distant Carita Beach, West Java, where are recorded on analog form. We used ink paper recording and sample recording on magnetic tape. Additionally, the envelopes of seismograms are also digitally recorded To get more detailed seismic information about the source of activity, sporadic measurements at Anak Krakatau island have been carried out in the periods December 1992, May and August 1993, using a 5 second (semibroadband) 3 component seismometer (Le3D15s). These measurements were also accompanied by visual observations, acoustic noise and video recordings. In this paper we tried to analyze-the pattern of eruptions. Through the use of phase space reconstruction, we examine the relation between eruption intervals. We conclude that the phase space portraits of Anak Krakatau eruptions, obtained by applying reconstructive techniques to shock interval data during the activity clearly illustrate the deterministic chaotic nature of the system. A simple conceptual model of volcanic eruption behaviour was also presented In order to approach the source time function of eruption, we tried to restitute the signals to reduce response of the instrument. As the seismograms were recorded on a site of less than 1 km distance to the source, the station is still in the near field Therefore, the restituted ground displacement seismogram approaches the source time function (wavelet), at least in the initial phase.